2013
DOI: 10.1128/aem.02645-12
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Bacillomycin D in Bacillus amyloliquefaciens SQR9 to Antifungal Activity and Biofilm Formation

Abstract: cBacillus amyloliquefaciens strains are capable of suppressing soilborne pathogens through the secretion of an array of lipopeptides and root colonization, and biofilm formation ability is considered a prerequisite for efficient root colonization. In this study, we report that one of the lipopeptide compounds (bacillomycin D) produced by the rhizosphere strain Bacillus amyloliquefaciens SQR9 not only plays a vital role in the antagonistic activity against Fusarium oxysporum but also affects the expression of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
143
2
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(158 citation statements)
references
References 35 publications
(53 reference statements)
3
143
2
10
Order By: Relevance
“…The sharper decreases in 344 countings when sterile and non-sterile conditions were compared suggest this isolate has a lower competitive ability than 629. Indeed, several studies show that species of Bacillus produce more antimicrobial compounds than species of Enterobacter (Xu et al, 2013). Our previous greenhouse studies with these two bacteria in cacao seedlings have also shown higher growthpromotion and stress-reduction effects for 629 than for 344 (Leite et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The sharper decreases in 344 countings when sterile and non-sterile conditions were compared suggest this isolate has a lower competitive ability than 629. Indeed, several studies show that species of Bacillus produce more antimicrobial compounds than species of Enterobacter (Xu et al, 2013). Our previous greenhouse studies with these two bacteria in cacao seedlings have also shown higher growthpromotion and stress-reduction effects for 629 than for 344 (Leite et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the AKP activity, conductivity and protein contents were measured; and results suggested that iturin A undermined the integrity of the fungal cell wall and membrane, causing leakage of the contents. Antibiotics in the iturin family were found to act upon sterols presenting in the cytoplasmic membrane of microorganisms [38]. Although cell membrane was the most significant defense and prime sites for antimicrobial attack, destroy of fungal cell wall was also seriously targeted for antifungal activity.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, we can see the peak of FPII in MHT88 is higher than that in MHT6. The fractions obtained from the MHT6 and MHT88 were separately tested for their inhibitory activity by oxford cup method (Xu et al, 2013). The results given in Table 4 showed that fraction FP-II showed significant inhibitory activity against the growth of F. moniliforme L8.…”
Section: Antifungal Activity Of Fraction Separated By Fplcmentioning
confidence: 99%
“…The antagonistic ability of MHT6 fermentation broth against F. moniliforme L8 was tested by culture filtrate test using oxford cup method (Yoshida et al, 2001;Xu et al, 2013). The MHT6 was inoculated in 250mL nutrient broth at 37°C for 72 h. After centrifuging the culture at 10,000 g for 10 min, supernatant was collected and filtered through a 0.22 μm cellulose nitrate filters under sterile conditions.…”
Section: Antagonistic Activity Of B Megaterium Mht6 Cell Against F mentioning
confidence: 99%
See 1 more Smart Citation